Analysis of the Effect of CVT Spring Variation on the Performance of Beat Deluxe Motorcycles - Maulana, Aceng Anrul; Martoni (R.E.M. (Rekayasa Energi Manufaktur) Jurnal, 2025)
Automatic motorcycles are popular due to their efficiency and flexibility in urban areas. CVT spring modifications are often done to improve performance. This research tested the effect of 1000 RPM (standard), 1500 RPM, and 2000 RPM CVT springs on a Beat Deluxe using a dynotest, observing torque, power, fuel consumption, CVT wear, and engine temperature on 68 kg and 134 kg riders. The results showed that at 3000 RPM, the highest torque was achieved by the 2000 RPM spring (14.04 Nm for 68 kg, 12.84 Nm for 134 kg). The highest power at 4000 RPM was also by the 2000 RPM spring (6.6 HP for 68 kg, 5.9 HP for 134 kg) but with the highest fuel consumption (0.021 l/km for 68 kg, 0.030 l/km for 134 kg). The 1500 RPM spring showed a moderate performance increase with wear and temperature between the 1000 RPM and 2000 RPM springs. The 1000 RPM spring produced the lowest temperature (76.5 ℃), followed by 1500 RPM (79.7 ℃) and 2000 RPM (84.1 ℃), indicating a correlation between spring stiffness and operating temperature.